The Precambrian, Eocambrian and Early Palaeozoic Stratigraphy of the Jørgen Brønlund Fjord Area, Peary Land, North Grenland. - Jepsen, Hans F. (Meddelelser om Grønland, 1971)
The sedimentary sequence in the platform area (approx. 2500 km2) around Jørgen Brønlund Fjord, North Greenland, has been mapped, and sections through the Precambrian, Eocambrian and Lower Palaeozoic sequence are described. After a summary of the previous geological field work carried out in the area, a lithological description of a composite section through the sequence below the Lower Cambrian Brønlund Fjord Dolomite (TROELSEN, 1949) is given. This sequence, which is about 1000 m thick, is divided into four formations-in ascending order: Inuiteq Sø Formation (sandstone), Morænesø Formation (tillite and dolomite), Portfjeld Formation (dolomite) and Buen Formation (sandstone and shale). The first three named formations are separated by two unconformities both representing a long period of erosion. The strata are cut by two dolerite sequences, of which the older (the Midsommersø dolerites) is of Precambrian age and intrudes only the Inuiteq Sø Formation. Intrusions of the younger sequence penetrate all the strata in the Jørgen Brønlund Fjord area and are regarded as post-Palaeozoic. In the last section the chronostratigraphy and the correlation with neighbouring areas are discussed. Special attention is given to the two newly discovered erosional unconformities, which together with the tillite occurrence and the radiometric K/Ar dated Midsommersø dolerites, throw new light on the stratigraphy of North Greenland.